Administration of ketoprofen affects post‐partum lying behaviours of Holstein dairy cows regardless of whether parturition is assisted. (19th April 2021) - Gladden, Nicola; Ellis, Kathryn; Martin, Jessica; McKeegan, Dorothy
Abstract: Background : Assistance at parturition in cattle is common. Although analgesia is commonly provided, its value in terms of welfare improvement is not known. Few previous studies include both parturition assistance and analgesic treatment status as well as appropriate control groups in a factorial design. Methods : Seventy‐two Holstein cattle (37 assisted and 35 unassisted) were randomly allocated to receive a single dose of the NSAID ketoprofen or a saline placebo within 3 h of parturition. Detailed behavioural observations allowed a time budget to be constructed for each cow for 48 h post‐partum. Results : Cows experiencing assisted parturition spent more time in lateral recumbency (overall and with the head rested) ( p < 0.05) – an infrequently adopted posture suggestive of illness or pain. Cows treated with ketoprofen spent less time in lateral recumbency ( p < 0.05) (overall and with the head rested); this was independent of assistance status, and lateral recumbency was not affected by the interaction between assistance and treatment status. Additionally, cows treated with ketoprofen spent more time with the head rested when in sternal recumbency ( p = 0.009) – a behaviour associated with comfortable resting. Conclusion : These differences in lying postures exhibited by cows receiving ketoprofen analgesia suggest that, regardless of whether parturition is assisted, a single dose of ketoprofen in the immediate post‐partum period has the potential to improve cow comfort in the first 48 h post‐partum.